One Country, One Vote? Labor Market Structure and Voting Rights in the ECB - Helge Berger; Carsten Hefeker (Center for Economic Studies and ifo Institute (CESifo), 2004)
The pending enlargement of the European Monetary Union (EMU) has brought to the fore the discussion of the voting right distribution in the European Central Bank (ECB) council. We show that, in a model where labor unions internalize the inflationary consequences of wage setting, deviating from a voting scheme based purely on economic size can be beneficial. Preliminary evidence on unemployment and voting rights in the ECB council seems broadly in line with this idea. We also point to possible policy implications for EMU enlargement and ECB restructuring.
Keywords: 330; monetary policy; wage setting; European Monetary Union; European Central Bank; euro area; ECB reform; EMU enlargement; accession countries